Seven steps to strategic SDG sensemaking for cities - Ville Taajamaa; Minna Joensuu; Barbara Karanian; Luís M. A. Bettencourt (Administrative Sciences, 2022)
This practitioner paper is based on the need to make sense of UN Agenda 2030 and Sustainable Development Goals (SDGs) at the city level and in an urban context. We examine the need to explain how to utilise the SDGs in strategic, tactical and operative urban development. We find that there are knowledge and practise gaps in how to localise SDGs in the urban context. This need and the lack of existing tools has led to the development of a strategic sensemaking process, which has been tested and developed with municipal and other practitioners, locally and globally. The paper presents findings from this process of development and from implementation pilots, including an SDG Sensemaking Tool (SST), a step by step iterative procedure to address these gaps. The main focus of this paper is the SDG Sensemaking process, which relies on analysing SDGs in relation to any given phenomena or project within or outside a city. The first results in this work-in-progress show that it contributes to an understanding on the complexity of how SDGs are related to the analysed phenomena, and catalyses the SDG localisation process, which helps make sense of how to navigate and measure progress in such complex environments. More research and applications are, however, needed, so as to further understand how urban governance can meet holistic, sustainable-development needs. Future work will, firstly, comprise further integrating SDGs into city-level strategies with a focus on the local, regional, national, and global impact on sustainable development and the actualisation of SDGs, and secondly, on further developing SST so that it can serve these purposes.
Keywords: 350; 2030 UN Agenda & SDGs; localizing SDGs; storytelling and strategy; strategic sensemaking; urban sustainable development